Glue Sniffing Neuropathy in an 18-Year-Old Male Butcher with a History of Weed Smoking: Case Report - Allareddy Sathvika; Uma.M.Anand Kumar; Arun Pandiyan M (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Glue sniffing neuropathy, a consequence of volatile substance abuse, presents with peripheral nerve damage. We present a case of an 18-year-old male butcher with a history of chronic glue sniffing and occasional marijuana use. He presented with a three-month history of progressive muscle weakness, small muscle wasting, hypotonia, hyporeflexia, and ascending quadriparesis. This case highlights the neurological repercussions of inhalant abuse, particularly in adolescents.